2009
DOI: 10.1038/cr.2009.58
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium transporter AtMGT9 is essential for pollen development in Arabidopsis

Abstract: Magnesium (Mg 2+ ) is abundant in plant cells and plays a critical role in many physiological processes. A 10-member gene family AtMGT (also known as AtMRS2) was identified in Arabidopsis, which belongs to a eukaryote subset of the CorA superfamily, functioning as Mg 2+ transporters. Some family members (AtMGT1 and AtMGT10) function as high-affinity Mg 2+ transporter and could complement bacterial mutant or yeast mutant lacking Mg 2+ transport capability. Here we report an AtMGT family member, AtMGT9, that fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 36 publications
1
79
0
Order By: Relevance
“…Most plant genomes encode multiple MIT proteins (Schock et al 2000;Li et al 2001). The Arabidopsis plasma membrane protein AtMGT1 (Li et al 2001), the chloroplast inner membrane protein AtMrs2-11 (Drummond et al 2006), and the mitochon-drial protein AtMgt5 (Chen et al 2009) have all been shown to play important roles in Mg homeostasis, but the function of many other members of this large gene family remains unknown. The identification of a functional homolog of Mnr2 in plants would further advance our understanding of Mg homeostasis in higher eukaryotes as well as provide a potentially useful tool to manipulate the nutrient content of economically important species.…”
mentioning
confidence: 99%
“…Most plant genomes encode multiple MIT proteins (Schock et al 2000;Li et al 2001). The Arabidopsis plasma membrane protein AtMGT1 (Li et al 2001), the chloroplast inner membrane protein AtMrs2-11 (Drummond et al 2006), and the mitochon-drial protein AtMgt5 (Chen et al 2009) have all been shown to play important roles in Mg homeostasis, but the function of many other members of this large gene family remains unknown. The identification of a functional homolog of Mnr2 in plants would further advance our understanding of Mg homeostasis in higher eukaryotes as well as provide a potentially useful tool to manipulate the nutrient content of economically important species.…”
mentioning
confidence: 99%
“…The story became even more fascinating when Chen et al [3] described a second Mg 2+ transporter, AtMGT9, which also affected pollen viability. AtMGT9 supported the growth of the bacterial MM281 mutant at 500 µM Mg 2+ , but not at 10 µM Mg 2+ , reminiscent of a low-affinity transporter.…”
mentioning
confidence: 99%
“…As with AtMGT5, disruption of AtMGT9 led to pollen abortion, and only hemizygous mutants survived. Crossing experiments proved that the mutated atmgt9 allele could not be transmitted through the pollen due to lack of fertility [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations